Progress on implementing and using electronic health record systems Developments in OECD countries as of 2021 - Slawomirski, Luke (OECD Publishing, 2023)
Electronic Health Records (eHR) represent a significant digital transformation in the healthcare sector. A 2021 OECD survey of 27 countries revealed a growing adoption of eHRs. However, system fragmentation remains a concern: only 15 countries have a nationally unified system. Twenty-four countries have adopted a minimum data set for standardized core health information. While patient access to eHRs has notably increased since 2016, obstacles such as provider resistance, technical barriers, and legal hurdles continue to exist. The COVID-19 pandemic underscored the pivotal role of eHRs, particularly in vaccine tracking and post-market surveillance, highlighting the pressing need for international cooperation to maximize the benefits of eHRs in healthcare. Furthermore, as eHRs integrate with artificial intelligence, new governance challenges arise
Keywords: Social Issues/Migration/Health